Konsep Manajemen Bisnis dan Marketing Syariah (Elaborasi Terhadap Lembaga Pendidikan Islam) - Mohammad Kuswadi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
Business according to Islam is a lawful thing even highly recommended. Business was even carried out by the prophet and the Prophet's apostle who was a very respected merchant of his day. Islam allows business as long as it is not things that lead to usury, gambling, the provision of products or services that contain illicit goods. In business, of course, a marketing is needed. The basis of Shari'ah marketing activities must be; 1). The spirit of worship to Allah Swt, 2). Try as much as possible for the common welfare, 3). Not for the benefit of the group let alone their own interests. Marketing is an important aspect in a business practice. Business practices not only focus on the problem of product sales (sales performance orientation) that are quality and meet the needs and desires of customers, but there is also a process of communication that continues to proactively foster a series of business networks through marketing products or services that can impress customers (customer loyality). Marketing is often interpreted as sales. Understanding of marketing actually wider and sales activities. Sales are a part of marketing activities. Marketing does not only cover the activities of selling goods or services, but includes several other activities that are quite complex such as; 1). research on consumer behavior, 2). research on market potential, 3). activities to develop new products, and 4). distributing and promoting goods sold. Marketing strategy is a form of directed plan in the field of marketing, to obtain an optimal result. The marketing strategy contains two separate but closely related factors, namely, the target market and the marketing mix. These two factors are closely related. The target market is the target to be addressed, while the marketing mix is ​​a tool to get to that target. Marketing strategy has a broad scope in the field of marketing. Among them are strategies in competition, product strategies, and so on.